BUDAYA AGRARIA INDONESIA - Robit Nurul Jamil (Jantra., 2019)
The Basic Agrarian Law which has been effective after the Indonesian Revolution in 1945, should have provided an access to land ownership and a fair return to the farmers. However, at every important point in the history of modern Indonesia, land ownership and access to it have become important issues which create a strong tension between the elites and the common people, between the interest of the local and that of the central government, and between local and international businesses. “Land for the people” is a common revolution idiom that is often used. In Indonesia, the response to the territorialisation by the government is sometimes harsh with ruthless actions. These confrontations indicate that the issues of fundamental rights cannot be solved. To find the solution, ideas from Zonder ‘Exploitation De L‘Homme Par L‘Homme’ and ‘Exploitation De Nation Par Nation’ are needed. Using descriptive analysis method, this qualitative research focused on the examination on 1) Revitalization of Agraria and 2) the principles of Zonder ‘Exploitation De L‘Homme Par L‘Homme’ and ‘Exploitation De Nation Par Nation’. The result of this research is all agrarian confrontation have to prioritize the orientation of Zonder ‘Exploitation De L‘Homme Par L‘Homme’ and ‘Exploitation De Nation Par Nation’ as a means to create a just and prosperous society.